1998
DOI: 10.1038/sj.ijo.0800668
|View full text |Cite
|
Sign up to set email alerts
|

The effects of dietary-induced obesity on the biomechanical properties of femora in male rats

Abstract: OBJECTIVE: To assess the effects of diet-induced obesity (DIO), on the biomechanical and biochemical properties of the femur in mature male rats. DESIGN AND SUBJECTS: Two groups of male rats were studied. The DIO experimental group was fed a high caloric diet and a 31% sucrose solution as drinking¯uid for a month, whereas the control group was fed lab chow and tap water. MEASUREMENT: Body weight; body water; lean body mass; femoral length; average cortical thickness; outer anteroposterior diameter; outer medio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 17 publications
5
15
1
1
Order By: Relevance
“…In addition to previous studies of the skeletal effects of obesity, the current study specifically examined the effects of increased intakes of calcium and vitamin D -key dietary components essential for bone health -on bone status and its regulation in DIO. The results obtained show that the weight of long bones (tibia and femur) was increased, although not significantly, in DIO mice, which is consistent with other studies evaluating bone status in obesity [42][43][44]. More significantly, the relative bone weight and the bone calcium and phosphorus content were dramatically decreased in the DIO group.…”
Section: Discussionsupporting
confidence: 90%
“…In addition to previous studies of the skeletal effects of obesity, the current study specifically examined the effects of increased intakes of calcium and vitamin D -key dietary components essential for bone health -on bone status and its regulation in DIO. The results obtained show that the weight of long bones (tibia and femur) was increased, although not significantly, in DIO mice, which is consistent with other studies evaluating bone status in obesity [42][43][44]. More significantly, the relative bone weight and the bone calcium and phosphorus content were dramatically decreased in the DIO group.…”
Section: Discussionsupporting
confidence: 90%
“…A study of bone biomechanics in adult rats with diet-induced obesity showed significantly greater bone strength in the obese rats than in the controls. The cross-sectional geometry and ultimate fracture load of the femur were higher in the obese rats than in the controls [8]. In our study, however, there were no significant differences in trabecular and cortical bone mass between the leptin-deficient obese mice and the leptin-deficient control mice.…”
Section: Discussioncontrasting
confidence: 75%
“…Surprisingly, only a few studies have addressed this question using animal models. Rat studies have found reductions in yield and maximum stresses, energy absorption, structural rigidity and failure loads, despite larger bone sizes as a result of high-fat and high-sugar diet-induced obesity [17,18,19]. Conclusions have not always been consistent; however, in general, a significant decrease in mechanical performance (reduced bone quality) concurrent with an increase in bone size (increased bone quantity) has been reported.…”
Section: Introductionmentioning
confidence: 99%